Analisis Nilai Karakter Film”Battle of Surabaya” Sebagai Media Pembelajaran PPKn Kelas 6 Sekolah Dasar - Alfan Setiyawan; Hamidaturrohmah, Hamidaturrohmah; Nina Sofiana (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
The teacher's challenge in implementing character education in elementary schools is increasingly complex. Planting character requires the right way so that it can be internalized in students so that it can become a habit. This study aims to analyze the value of the characters in the film "Battle of Surabaya" as a medium for learning PPKn grade 6 elementary school. This research uses a qualitative approach in the form of descriptive analysis. The data used consisted of primary data in the form of the film "Battle of Surabaya", teacher's books and books for grade 6 elementary school students. Supported by secondary data in the form of previous research and reference books. The results of this study found that the film "Battle of Surabaya" can be used as a media for learning PPKn for grade 6 elementary school. Character education reflected in the film scenes represents religious character, responsibility, honesty, social care, love for the motherland, hard work, tolerance, friendship or communicativeness, all of which are shown in the film "Battle of Surabaya". So that the film "Battle of Surabaya" is very feasible and suitable to be used as an innovative learning media for PPKn grade 6 elementary schools through joint movie learning activities.